The association between vaccination status identification and societal polarization - Luca Henkel; Philipp Sprengholz; Lars Korn; Cornelia Betsch; Robert Böhm (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Public discord between those vaccinated and those unvaccinated for COVID-19 has intensified globally. Theories of intergroup relations propose that identifying with one's social group plays a key role in the perceptions and behaviors that fuel intergroup conflict. We test whether identification with one's vaccination status is associated with current societal polarization. The study draws on panel data from samples of vaccinated (n = 3,267) and unvaccinated (n = 2,038) respondents in Germany and Austria that were collected in December 2021, February, March, and July 2022. The findings confirm that vaccination status identification (VSI) explains substantial variance in a range of polarizing attitudes and behaviors. VSI was also related to higher psychological reactance toward mandatory vaccination policies among the unvaccinated. Higher levels of VSI reduced the gap between intended and actual counter-behaviors over time by the unvaccinated. VSI appears to be an important measure for predicting behavioral responses to vaccination policies.
Keywords: D91; 330; Vaccination; Identification; Discrimination; Mandates; COVID-19